Long‐term effect of tillage and straw retention in conservation agriculture systems on soil carbon storage. Issue 5 (9th September 2021) - Gómez‐Muñoz, Beatriz; Jensen, Lars Stoumann; Munkholm, Lars; Olesen, Jørgen Eivind; Møller Hansen, Elly; Bruun, Sander
Abstract: The main principles of conservationagriculture (CA) are minimal soil disturbance, permanent soil cover, diversification of crop rotations, and retention of crop residues. Tillage has been implicated with increased soil organic C (SOC) mineralization, but recently this has been contested. Residue retention and cover crops result in higher soil C inputs and are therefore expected to increase SOC. This study aimed to evaluate the effect of 17 yr of residue retention (with and without) and tillage (plowing and no‐till) on soil C storage on two Danish sandy loam soils with different clay and SOC content under cool temperate humid climate conditions. Straw retention reduced bulk density at both sites. It also increased the C concentration with 0.47 mg C g –1 dry soil on average from 2002 to 2019, and SOC stocks in 2019 with 23 tonnes C ha –1, on average, at the site with higher initial SOC content. The effect of straw retention on soil C was higher when the soil was plowed, and no significant effect was observed in no‐till soils. Straw retention did not significantly affect C concentration at the site with low initial SOC. Tillage altered the C distribution in the soil profile, so that the C concentration in the upper layer (0–25 cm) was higher in the no‐till soils, but did not significantly increase total C concentration in deeper layers (0–50 cm). Use of no‐till and straw retention did not consistently affect crop yield across site‐years, but the interannual variability was large, obscuring possible differences in yields. Core Ideas: Straw retention reduced soil bulk density at sites with low or medium‐high initial C level. Straw retention increased C concentration and SOC stock at a site with higher C. Tillage altered soil profile C distribution but did not increase SOC storage. Yield was not affected by 17 yr of no‐till and straw retention.